Variations in the quantity and quality of Persian wheat genotypes under normal irrigated and rain-fed conditions (Bioagro, 2020)
The importance of wheat in providing staple food for many populations is not disputed, but drought stress can significantly reduce the yield and quality of the grain. Thirty one genotypes of bread wheat were examined under normal irrigated and rain-fed conditions for their protein, Fe, Zn, Cu, Mn, P, Na and K grain concentrations. The experiment was conducted as a split-plot (irrigated and rain-fed as main plots and 31 cultivars as sub-plots) in a randomized complete block design with three replications in Sanandaj, Kurdistan, Iran, during the 2013–2014 cropping season. Based on a two-way Anova, we found large inter-genotype variations among the traits. Significant differences were also observed for the genotypes between normal irrigated and rain-fed conditions. Except for the grain protein concentration, which showed only a 1.93 % increase, the rain-fed conditions negatively affected each of the other traits significantly. Major effects were found for grain yield, number of grains per spike and grain Zn concentration, showing 43.09 %, 27.74 % and 23.88 % reductions, respectively. Negative correlations were observed between grain yield and grain protein, Fe, Zn, Cu, Mn, P and Na concentrations. Our data show that breeding for higher tonnage-yield during the past 80 years has brought success but at the cost of lower concentrations of protein and microelements in the wheat grains.
Keywords: Dryland cropping; grain quality; micronutrients; plant nutrition; PCA